A Feasibility Study on the Offering DITM Doctor of Industrial Technology Management (DITM) at the Graduate School Bulacan State University-Main Campus - Maroma, Allen N.; Galita, Warlito M.; Maroma, Dolly P. (Future Science / FSH-PH Publications, 2024)
This study investigates whether the Graduate School of Bulacan State University-Main Campus could provide a Doctor of Industrial Tech-nology Management (DITM) program. The study's goals were as-sessing the demand for a DITM program, examining comparable ser-vices in the area, performing financial and managerial analysis, and creating a suggested curriculum. Results indicate strong interest from prospective registrants, supporting the demand for the program. The program was established with additional help from thoroughly exam-ining competing programs, financial sustainability, and operational logistics. To advance technology management education and give stu-dents a variety of abilities to solve market difficulties, BulSU imple-mented DITM. By encouraging cooperation between public and com-mercial organizations, the initiative would cultivate the growth of highly qualified professionals who could lead responsible and sus-tainable technology management practices. As a result, this initiative would contribute positively to the community and the broader indus-trial landscape.